PERANCANGAN APLIKASI DUTA BANGSA E-KANTIN SEBAGAI MEDIA KOMUNIKASI DIGITAL BERBASIS ANDROID - Kusuma, Adri Surya; Solichin, Mamat Nur; Yuliana, Margaretha Evi (IDEALIS : InDonEsiA journaL Information System, 2024)
The technology developed very rapidly to be able to change communication skills. The appearance of an application's user interface can be a media for how digital interaction and communication is carried out today. Android-based applications have been created and used in various fields. This research was conducted on the process of ordering food with the scale of the canteen area of each faculty at Duta Bangsa University Surakarta where the process is currently still conventional which requires customers or students to come to the canteen.The research aims to design an e-canteen Duta Bangsa application as an android-based digital communication media. The research method uses Research and Development (R&D) with Blackbox Testing on the system and the SUS (System Usability Scale) method used in usability measurements. The results that have been achieved in this study are the prototype of the Duta Bangsa e-Canteen application with 3 user level access rights, namely admin, canteen branches, and customers. The percentage of user satisfaction based on the Likert scale is 85,33% of 30 respondents. This shows that the applicationcan provide easeof communication and transactions between canteen brances and customers or users of the application. Food ordering can now be done virtually through an application interfaceas a result of advancein digital communication technology.